DeweyTP: a labeling scheme for probabilistic XML data - Zi-yang CHEN; Jia LIU; Liu-hui ZHANG; Jun-feng ZHOU (Tongxin xuebao)
Compared with ordinary XML documents, nodes in the probabilistic XML documents have two characteristics, the type of nodes was non-unique and the nodes exist with a corresponding probability. As an efficient labeling scheme, DeweyTP was proposed to assign each node a unique label, which contains the type and path probability of nodes, supporting the detection of node type and the extraction of path probability, and thus improves the system performance. Finally, experimentally evaluated DeweyTP encoding scheme were experimentally evaluated in aspects of time and space efficiency.